Dependence of Performance of Si Nanowire Solar Cells on Geometry of the Nanowires - Firoz Khan; Seong-Ho Baek; Jae Hyun Kim (The Scientific World Journal)
The dependence of performance of silicon nanowires (SiNWs) solar cells on the growth condition of the SiNWs has been described. Metal-assisted electroless etching (MAE) technique has been used to grow SiNWs array. Different concentration of aqueous solution containing AgNO3 and HF for Ag deposition is used. The diameter and density of SiNWs are found to be dependent on concentration of solution used for Ag deposition. The diameter and density of SiNWs have been used to calculate the filling ratio of the SINWs arrays. The filling ratio is increased with increase in AgNO3 concentration, whereas it is decreased with increase in HF concentration. The minimum reflectance value achieved is ~1% for SiNWs of length of ~1.2 μm in the wavelength range of 300–1000 nm. The performance and diode parameters strongly depend on the geometry of SiNWs. The maximum short circuit current density achieved is 35.6 mA/cm2. The conversion efficiency of solar cell is 9.73% for SiNWs with length, diameter, and wire density of ~1.2 μm, ~75 nm, and 90 μm−2, respectively.